2020
DOI: 10.1097/md.0000000000020626
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the status of oral intake management measures during labor in China

Abstract: The World Health Organization recommended that the oral intake of low-risk pregnant women during labor should not be restricted. Hospitals in different countries take different measures to manage the intake during labor, but it is not clear about the current situation of oral intake management measures in the hospital during labor in China. Thus, the objective of this study was to investigate the current situation of oral intake management measures during labor in China, so as not only provide references for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Studies have shown that the oral intake of a high‐calorie liquid during the second stage of vaginal delivery enhances uterine contractility, shortens the birthing process, promotes postpartum uterine contraction, and reduces the postpartum hemorrhage rate. Adequate energy is the material basis of and an inherent condition for muscle contraction, supporting the finding that oral carbohydrates promote uterine contractility and reduce vaginal bleeding 19,20 …”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Studies have shown that the oral intake of a high‐calorie liquid during the second stage of vaginal delivery enhances uterine contractility, shortens the birthing process, promotes postpartum uterine contraction, and reduces the postpartum hemorrhage rate. Adequate energy is the material basis of and an inherent condition for muscle contraction, supporting the finding that oral carbohydrates promote uterine contractility and reduce vaginal bleeding 19,20 …”
Section: Discussionmentioning
confidence: 55%
“…Adequate energy is the material basis of and an inherent condition for muscle contraction, supporting the finding that oral carbohydrates promote uterine contractility and reduce vaginal bleeding. 19,20 Preoperative oral carbohydrate consumption reduces postoperative muscle loss, promotes muscle strength, 21 and facilitates early physical activities (out of bed). We recommend administering patient-controlled analgesia before the patient gets out of bed.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that patients with gastrointestinal dysfunction have a lower incidence of gastroesophageal re ux and vomiting after eating semi-solid food than after consuming liquids [10][11]. Consistent with the dietary culture in China, for many years most parturients have eaten semi-solid food during labor [12]. Chewing and stimulation of chyme can promote gastrointestinal peristalsis [13] ,relieve anxiety and discomfort caused by hunger, and reduce excitement of the sympathetic nervous system.…”
Section: Discussionmentioning
confidence: 96%
“…In china, for example, childbirth is traditionally considered as a process in which the mother continuously consumes energy, and supplementing food is beneficial. Therefore, a relatively liberal oral intake policy on the labor ward is adopted in about 77% hospitals in China, [ 6 ] which may significantly increase the risk of aspiration when general anesthesia is required unexpectedly.…”
Section: Introductionmentioning
confidence: 99%